INSTACLASS INCORPORATING INSTAGRAM AS A MOBILE LEARNING TOOL IN LANGUAGE CLASSROOM - Kun Mustain; Af'idatul Husniyah; Zubaidi . (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
Technology has shifted teacher-centered approach to a more student-centered learning, where students construct their own understanding and acquire new language while also building networks and socializing with their peers in a meaningful communication. This mixed-method research aimed to explore students’ perspectives in using Instagram as a platform to learn English. The findings of the research showed that most students felt more motivated in learning English in classrooms where Instagram is integrated as a learning tool. More importantly, students also felt more engaged in meaningful communication during the learning process, which is in accordance with the previously conducted studies. Students also revealed that Instagram can promote meaningful interaction as well as learner autonomy which are essential for their life outside the classroom.